Home care: uma análise - Ozaki, Veridiana Tonzar Ristori [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present work aims to study the bioethical implications of home care, when considered a form of health care, to protect Human Rights. Currently, home care is considered a modern practical assistance, both by health plans in the private sector and by public health sector policies. Home care represents a trend worldwide and in Brazil, it states humanization in attendance, release of hospital beds, infection rates reduction and patient quality of life improvement as advantages for its implementation. However, we try to understand how home care presents several moral and ethical issues related to the actors involved: the patient, the caregiver, the family and the multidisciplinary team. The work resorts to Bioethics of Intervention and Bioethics of Protection, two Bioethics strands developed after Principlism was proved insufficient in a context of large of social inequalities, which is the case of Brazil. From this perspective, it is possible to give a voice to the excluded, oppressed and vulnerable. It is in this sense that bioethics must resort to human rights, as a way to protect the right to health of the neediest. Thus, it is sought to demonstrate that Home Care is a sector that has vulnerable subjects (patient, caregiver, family), to which the public protection policies should be directed

O presente trabalho tem por objetivo estudar as implicações bioéticas do home care, como modalidade de assistência de saúde, buscando-se tutelar os Direitos Humanos. Atualmente, o home care é considerado uma prática moderna de assistência, tanto pelos planos de saúde do setor privado, quanto pelo setor das políticas públicas de saúde. Representa uma tendência no mundo e no Brasil e traz o discurso da humanização no atendimento, liberação de leitos hospitalares, redução dos índices de infecção e melhoria da qualidade de vida dos pacientes como vantagens para sua implementação. Todavia, busca-se compreender que o home care apresenta uma série de problemáticas morais e éticas relacionadas aos atores envolvidos: o paciente, o cuidador, a família e a equipe multiprofissional. O trabalho recorre à Bioética de Intervenção e à Bioética da Proteção, vertentes da Bioética que foram desenvolvidas a partir da constatação que a Bioética Principialista se mostrava insuficiente frente a contextos de grande desigualdade social como é o caso do Brasil. Por essa perspectiva, é possível dar voz aos excluídos, oprimidos e vulneráveis. É, nesse sentido, que a Bioética deve recorrer ao referencial dos Direitos Humanos, como forma de tutelar o direito à saúde dos mais necessitados. Dessa forma, procura-se demonstrar que o Home Care é um setor que apresenta sujeitos vulneráveis (paciente, cuidador, família), aos quais as políticas públicas de proteção devem estar voltadas
Keywords: Direito; Serviços de cuidados de saúde domiciliares; Direitos humanos - Aspectos jurídicos; Bioética; Saúde pública - Aspectos sociais; Direitos sociais; Law